2018
DOI: 10.21608/bjas.2018.179330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Rich Plasma in the Management of Psoriasis

Abstract: Psoriasis is a chronic immune-mediated disease affecting approximately 2-3% of general population. It is associated with significant negative impact on patient's physical and psychological quality of life along with vulnerability to co-morbidities such as cardiometabolic dysfunction, depression, and so on [1]. to evaluate the efficiency of platelet rich plasma (PRP) in the management of patients with chronic localized recalcitrant plaque psoriasis.This was a prospective pilot study conducted on 30 cases with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Regarding patient and physician satisfaction, patients in the PRP group exhibited significantly higher satisfaction levels with the treatment outcomes than those in the control group (p = 0.034). These findings were consistent with the satisfaction levels reported by physicians, who expressed a markedly higher satisfaction rate with patient outcomes in the PRP group than in the control group (p = 0.042) [29].…”
Section: Clinical Evidence Of Prp's Effectiveness In Treating Plaque ...supporting
confidence: 89%
See 3 more Smart Citations
“…Regarding patient and physician satisfaction, patients in the PRP group exhibited significantly higher satisfaction levels with the treatment outcomes than those in the control group (p = 0.034). These findings were consistent with the satisfaction levels reported by physicians, who expressed a markedly higher satisfaction rate with patient outcomes in the PRP group than in the control group (p = 0.042) [29].…”
Section: Clinical Evidence Of Prp's Effectiveness In Treating Plaque ...supporting
confidence: 89%
“…While several clinical studies have demonstrated the effectiveness of PRP therapy in treating plaque psoriasis, their smaller sample sizes have limited the overall understanding of the treatment's impact and the generalization of the results. Although the existing research has shown promising results, the general consensus among medical researchers is that larger, more extensive studies are required [26][27][28][29][30]34]. By increasing the sample size, researchers can establish more substantial evidence of the effectiveness of PRP therapy for plaque psoriasis and further assess the potential benefits and risks associated with the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations